Gasdermin D protects against Streptococcus equi subsp. zooepidemicus infection through macrophage pyroptosis - Xu, Guobin; Guo, Zheng; Liu, Yuxuan; Yang, Yalin; Lin, Yongjin; Li, Chunliu; Huang, Yunfei; Fu, Qiang (Frontiers in Immunology, 2022)
Streptococcus equi subsp. zooepidemicus (S. zooepidemicus, SEZ) is an essential zoonotic bacterial pathogen that can cause various inflammation, such as meningitis, endocarditis, and pneumonia. Gasdermin D (GSDMD) is involved in cytokine release and cell death, indicating an important role in controlling microbial infection. This study investigated the protective role of GSDMD in mice infected with SEZ and examined the role of GSDMD in peritoneal macrophages in the infection. GSDMD-deficient mice were more susceptible to intraperitoneal infection with SEZ, and the white pulp structure of the spleen was seriously damaged in GSDMD-deficient mice. Although the increased proportion of macrophages did not depend on GSDMD in both spleen and peritoneal lavage fluid (PLF), deficiency of GSDMD caused the minor release of the pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-18 (IL-18) during the infection in vivo. In vitro, SEZ infection induced more release of IL-1β, IL-18, and lactate dehydrogenase (LDH) in wild-type macrophages than in GSDMD-deficient macrophages. Finally, we demonstrated that pore formation and pyroptosis of macrophages depended on GSDMD. Our findings highlight the host defense mechanisms of GSDMD against SEZ infection, providing a potential therapeutic target in SEZ infection.